Revolution in Documentary Film in Quebec: On The Days Before Christmas by Stanley Jackson, Wolf Koenig and Terence Macartney-Filgate and Les Raquetteurs by Michel Brault and Gilles Groulx - Kościński, Jędrzej (Media - Culture - Social Communication, 2019)
The subject of this article is the beginning of a new movement in documentary cinema, which was made possible by new technologies, in which the filmed reality is feasibly not staged, and the sound is generally synchronized with the image. The author says that a division of this movement into American (direct cinema) and French (cinéma-vérité) variant is unjust for the filmmakers from Canada, whom he sees as the real revolutionaries of documentary expression. He substantiates it with analyses of two films from Quebec – The Days Before Christmas (1958, by Stanley Jackson, Wolf Koenig and Terence Macartney-Filgate) and Les Raquetteurs (1958, by Michel Brault and Gilles Groulx) – explaining the ways in which they developed techniques and stylistic devices in the following years of direct cinema.